Dampak Pernikahan Dini Terhadap Pendidikan di Desa Lamea Kecamatan Wewiku Kabupaten Malaka - Erdiana Yovita Luruk; Marten Tabun (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2023)
This study aimed to determine (1) the impact of early marriage on education, and (2) the factors caused early marriage in Lamea Village, Malacca District. This research employed a qualitative approach. The subjects of this study were 14 people consisting of 9 parents and 5 children who had early marriages. Data collection in this study were carried out by observation, interviews and documentation. Data were analyzed through data collection, data reduction, data presentation and conclusions. The results of this study indicate that early marriage has both positive and negative impacts. The positive impact of early marriage is to reduce the economic burden on parents. Meanwhile, the negative impact of early marriage is not being able to continue their education to a higher level, lack of confidence with their peers, and often experience disputes in their household. The causative factors of early marriage are economic cases in new families, low knowledge or education degrees, social environment, and promiscuity.